2020
DOI: 10.1371/journal.pone.0225866
|View full text |Cite|
|
Sign up to set email alerts
|

Heart rate variability helps to distinguish the intensity of menopausal symptoms: A prospective, observational and transversal study

Abstract: Heart Rate Variability (HRV) represents cardiac autonomic behavior and have been related to menopausal symptoms, mainly vasomotor symptoms and their imbalance to cardiovascular risk. It is not clear in the literature which index represents this imbalance and what is their involvement with the menopausal state. The aim of this study was to evaluate HRV in menopausal transition and post-menopausal symptoms with different intensities. This cross-sectional study was conducted in Rio Branco, State of Acre, Brazil f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…About age at menarche and age at menopause, both groups presented similar results to those found in the literature 5,9,10 . Socioeconomic differences observed have also been described in previous Brazilian studies 5,7,8,10 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…About age at menarche and age at menopause, both groups presented similar results to those found in the literature 5,9,10 . Socioeconomic differences observed have also been described in previous Brazilian studies 5,7,8,10 .…”
Section: Discussionsupporting
confidence: 81%
“…DES group had a lower BMI and a higher percentage of physical activity practitioners than the control group. Mean chronological age corroborated the studies [5][6][7] that analyzed hormonal relationships in postmenopausal women with DES. About age at menarche and age at menopause, both groups presented similar results to those found in the literature 5,9,10 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The HRV analysis in the time domain showed that the indexes (SDNN, RMSSD, pNN50) evaluated in this study were similar during the resting period comparing blind patients and normal vision subjects. The SDNN is considered a marker of the total power (variance) of the HRV, expressing the long-term component responsible for the variability in the period of registration of the HR [21]. The SDNN index were not different in blind and normal vision subjects during resting, intervention and recovery, and regardless the period appraised in this study, the SDNN values were above 50 ms and below 100 ms.…”
Section: Discussionmentioning
confidence: 53%